Current trends in epileptology: priorities, challenges, tasks and solutions - Avakyan G.N.; Belousova E.D.; Burd S.G.; Vlasov P.N; Ermolenko N.A.; Kissin M.Ya; Lebedeva A.V; Lipatova L.V.; Kiteva Trenchevska G (My University, 2019)
Within a field meeting of experts from the Russian branch of the League Against Epilepsy (RLAE), diagnostic and treatment aspects of epilepsy were discussed with the emphasis on the female population (girls, women of childbearing and older ages). All experts underscored the special features and unique needs of female patients with epilepsy. Experimental and clinical studies on efficacy and safety of traditional and novel antiepileptic drugs (AEDs) applied to women with epilepsy were discussed. It was commonly agreed that the new generation of AEDs did not yet find an appropriate place in the clinical practice, and that they were mainly used as add-on therapy in order to overcome drug resistance. The current use of AEDs in the treatment of epilepsy is, by large, not gender-specific and is not related enough to age, sociodemographic characteristics, and comorbid disorders. It should be noted that the new AEDs are addressed specifically to individual, socio-demographic, gender and clinical features of the patient. The potential of some AEDs (lamotrigine), in fact, remains underestimated by practitioners. Due to the current restrictions in using valproic acid, lamotrigine is the alternative medication for women with epilepsy. Having a balanced profile of efficacy and safety, lamotrigine is recommended as the first choice drug for initial therapy, as well as an alternative monotherapy for epilepsy in women.
Keywords: epilepsy; female epilepsy; RLAE; pregnancy; lamotrigine; Seizar; AED efficacy; major malformations; epilepsy comorbidity; bipolar; depression